Socio-Economic Conditions of Farmers’ of Bagalkot District and their Impact on Suicides - Gyanappa Huddar, Purnanand Nagappa Sangalad*, Malakajappa (Journal of Experimental Sciences, 2011)
The latest spate of suicides among farmers in India today is a manifestation of an underlying crisis in agriculture which is a result of the marginalization of agrarian economy in national policy since the economic reforms of the 90s. It has been pointed that Ã¢â‚¬Å“Agriculture is the mainstay of the Indian economy, agriculture and allied sectors contribute nearly 17.8 percent of Gross Domestic Product (GDP) of Indian, while about 65 to 70 percent of the population is dependent on agriculture for theirs livelihoodÃ¢â‚¬Â. The existing literature on the agricultural crisis provided several factors that are directly and indirectly responsible for the distress and disappointment among farmers. Unfortunately due to uncertainty of monsoon, non-availability of credit, increasing prices of seeds, pesticides and fertilizers, agriculture has become a most critical industry and farmers are suffering due to economic distress and they are committing suicide on large scale in different provinces of the country. While Indebtedness of the farmers seems to be the major reported cause, the reasons that prompt the farmers to borrow money from individuals rather than from institutions are varied and differ from place to place. So an in depth studies on the farmersÃ¢â‚¬â„¢ distress leading to suicides in Bagalkot District is need of our study, concern in the present study facing major problems in farming community.Ã‚Â 